Analisis Hukum Islam terhadap Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana Pasal 479 Tentang Pemerkosaan dalam Pernikahan - Sitti Qadryani; Qadriani Arifuddin; Sa’adal Jannah; Risdayani Idris (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to find out rape in marriage based on the draft criminal law code article 479, Islamic law analysis of article 479 of the draft criminal code law on rape in marriage. The type of research used in this research is descriptive qualitative, while the data collection method used is library research. The data analysis technique used is a normative conceptual and juridical approach. The results of the research show that marital rape is based on the draft Criminal Code Article 479, namely anyone who, by force or threat of violence, forces someone to have sexual intercourse with them. Islamic law analysis of article 479 of the draft law on criminal law regarding rape in marriage is contrary to Islamic law, this is referred to in nushūz, namely abandoning obligations as husband or wife, if there is no sharia reason, and husband and wife should behave well. each other, and do not commit acts that could threaten the soul. Islamic criminal law states that perpetrators can receive kisas or diat. The implication of this research is that, with the existence of the Draft Criminal Code Article 479, it is hoped that society, especially married couples, will be more careful in their actions, should respect each other and understand each other's conditions, so that there are no problems that can cause mental or physical violence, because apart from This is not in accordance with Islamic law, this has also become the government's concern so that the perpetrators can be sentenced to 12 years in prison.